Prinsip Mizan dalam Pemeliharaan Lingkungan: Telaah Tafsir Al-Azhar Pada Q.S. Ar-Rahman Ayat 7-9 - Abdul Rasyid; Moh. Bakir; Munawir (Jurnal test, 2025)
This study examines the principle of mizan in the context of environmental maintenance based on the interpretation of the verses of the Qur’an Q.S. Ar-Rahman verses 7-9 according to Hamka. The research method used is qualitative with a type of library research that is descriptive analytical with a tahlili (analytical) approach. The data collection technique used is documentation. The analysis technique uses content analysis. The results of this study are that mizan according to Hamka’s interpretation of Q.S. Ar-Rahman verses 7-9, means order and balance, which is the basis for human understanding in maintaining the surrounding environment. Hamka’s interpretation of the verse builds an understanding of human responsibility as caliphs on earth in ensuring the sustainability of nature. In his analysis, Hamka emphasizes the importance of maintaining the balance of nature and using resources wisely, not only for the benefit of the present, but also for future generations. The principles of Mizan include the mandate of Allah, human responsibility, avoiding a materialistic lifestyle and amar ma’ruf nahi mungkar.